RUTE EVAKUASI TSUNAMI MENGGUNAKAN ALGORITMA FLOYD WARSHALL (STUDI KASUS DI LUBUK BUAYA, PADANG) - Rahma Yulia; Indah Permata Sari; Mohamad Syafi'i; Lilis Harianti Hasibuan (UPT Penerbitan Universitas Jember, 2022)
One of Indonesia's vulnerable Tsunami areas is in Padang City. Padang City is a coastal city, which is located to the east of the Indian Ocean. It is close to the meeting of the Indo-Australian plate and Eurasian plate, which can trigger a powerful earthquake and generate a tsunami. Therefore, determination of the evacuation route is very important to do, particularly in Tsunami high risk areas. One of the highrisk areas is Lubuk Buaya District. The purpose of this research is to set the shortest route for tsunami evacuation as an effort to minimize disaster effects on local residents. The determination of the Tsunami evacuation route is done by forming a path graph, determining the weight of each path segment, and determining the shortest route using the Floyd Warshall Algorithm. The results obtained in this research are the safest and shortest Tsunami evacuation route that can be accessed by pedestrians, motorcyclists, and car drivers. Keywords: Evacuation Routes, Floyd Warshall Algorithm, Graph, Tsunami.